Evaluación del sistema de riego por microaspersión implementado en el jardín clonal de cacao (theobroma cacao l) ESPAM“MFL” - Zambrano Cedeño, José Javier (2012)
This research was conducted during the dry season of 2011 in the garden clonal cocoa Agricultural Polytechnic School of Manabí "Félix Manuel López," in order to evaluate the micro sprinkler irrigation system. Was raised as an objective, evaluate the technical efficiency of the irrigation system through proper management to support the increase in current production levels. Evaluations were components of the facility, which made it visually to determine the system status. The uniformity of irrigation on the area to be assessed and installation, reached 50.33 percent and 47.47% respectively. Evaporation losses and achieve a wind drag and 11.49% with respect to the thickness index of gout, a 27.77 obtained, indicating that they are too fine droplets. The optimum operating pressure of the system should be 25 psi and flow rate of 40 l / h. According to the design agronomic irrigation interval should be every day with a time of 21 minutes.